(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To compare ESBL and carbapenemase gene detection using phenotypic (double disc diffusion and VITEK-2AES), and genotypic (PCR) methods in the E. coli isolates in Nepal. Methods: 132 multidrug resistant E. coli isolates with phenotypic extended-spectrum-β-lactamase (ESBL) and carbapenemase archived during 2018 to 2023 at National Public Health Laboratory were analyzed to detect three extended-spectrum-β-lactamase genes (CTX-M, SHV and OXA 10/11) and eight carbapenemase genes (NDM, KPC, IMP, VIM, OXA‐51, OXA‐23, OXA‐48 and OXA‐58). Vitek 2 generated Advanced Expert SystemTM reports were compared with PCR findings, to evaluate their predictive diagnostic values. Results: Out of the 132 isolates tested, CTX-M gene was detected in 60/80 (75%), OXA 10/11 and SHV gene in none (0/80); while no genes were detected in 20 ESBL-non producers. NDM gene was detected in 12/22(55%) and OXA-48 in 2/22(9%) metallo-beta-lactamase (MBL) producers, while other carbapenemase genes were not detected in 10 MBL non-producers. Five (5%; 5/102) of the isolates had both CTX-M and NDM genes. The Vitek 2 detection of CTX-M-like ESBLs showed a sensitivity of 75% (60/80) and specificity of 100% (20/20) PPV of 100% and NPV of 50% for the E. coli isolates. Conclusion: blaCTX-M and blaNDM were the most common genes responsible for third-generation cephalosporins and carbapenem resistance respectively with low co-existence. Vitek2 AES detects ESBL with adequate sensitivity, however more evidences are required for use in routine screening.